Joint risk management and collaborative ethos: Exploratory research in the UK construction sector. Issue 2 (23rd September 2019) - Marinelli, Marina; Salopek, Marko
Abstract : Purpose: Based on experience from the UK construction industry, this paper aims to capture the dimensions of the collaborative ethos required for successful implementation of Joint Risk Management, i.e. the cooperative and dynamic risk management approach that continues into the post-contract stage and is jointly undertaken by different project stakeholders. Design/methodology/approach: A mixed methods research approach involving semi-structured interviews and a questionnaire survey was adopted to provide the basis for the statistical analysis encompassing descriptive statistics, non-parametric tests and exploratory factor analysis. Findings: The analysis highlights the critical role of team integration achieved through the diffusion of collaborative values at strategic and practical level. Relevant applications include early stakeholder engagement, common goals and interests, team building activities and contractual flexibility. Originality/value: This research is beneficial for the industry and academia as it enhances the understanding of an under-utilised management tool and highlights the requirements for its successful implementation.